2001
DOI: 10.1111/j.1469-7793.2001.0743h.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular carbonic anhydrase activity facilitates lactic acid transport in rat skeletal muscle fibres

Abstract: 1. In skeletal muscle an extracellular sarcolemmal carbonic anhydrase (CA) has been demonstrated. We speculate that this CA accelerates the interstitial CO 2 /HCO 3 _ buffer system so that H + ions can be rapidly delivered or buffered in the interstitial fluid. Because > 80 % of the lactate which crosses the sarcolemmal membrane is transported by the H + -lactate cotransporter, we examined the contributions of extracellular and intracellular CA to lactic acid transport, using ion-selective microelectrodes for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
62
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 45 publications
2
62
0
Order By: Relevance
“…A similar observation could be anticipated for any cell type with surface CA and a significant permeability to lactic acid, as schematized in Figure 2B. In skeletal muscle, 20 mM lactate produced an acid shift that was reduced by roughly half in the presence of 10 M benzolamide (Wetzel et al, 2001). By contrast, the LIA in astrocytes was virtually abolished by the same concentration of drug.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…A similar observation could be anticipated for any cell type with surface CA and a significant permeability to lactic acid, as schematized in Figure 2B. In skeletal muscle, 20 mM lactate produced an acid shift that was reduced by roughly half in the presence of 10 M benzolamide (Wetzel et al, 2001). By contrast, the LIA in astrocytes was virtually abolished by the same concentration of drug.…”
supporting
confidence: 82%
“…In a recent study of skeletal muscle by Wetzel et al (2001), inhibition of the surface CA by benzolamide reduced inward lactate-H ϩ cotransport, demonstrating that buffering of surface H ϩ by this enzyme was critical for inward operation of the monocarboxylate transporter. Since lactate-H ϩ carriers are also found on astrocytes and neurons (Broer et al, 1997), a similar dependence on extracellular buffering may be anticipated.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…In muscle cells, coexpression of CAII and acid/base-transporting proteins like NBC, NHE1, and also the MCTs have been found to be pivotal in acid/base homeostasis (20). In addition, it has been shown that extracellular carbonic anhydrase activity facilitates lactic acid transport in rat skeletal muscle fibers (21). In the brain CAII is highly expressed in astrocytes where it plays a supportive role in pH regulation (22) and supports the lactate shuttle from astrocytes to neurons (23).…”
mentioning
confidence: 99%